Treatment of gingival recession using enamel matrix proteins: a case report with 4-year follow-up - (:unkn) unknown (My University, 2007)
Obtaining predictable and optimal coverage of exposed root surfaces and correction of corresponding gingival recessions have become important goals of periodontal plastic surgery. Various surgical techniques have been proposed for coverage of root surfaces. A therapeutic advantage may be gained if periodontal regeneration is obtained in addition to coverage of root with gingiva. In this case report, surgical recession coverage was performed as the bilaterally pedicled lateral sliding flap technique with the adjunctive use of enamel matrix derivative bioactive material (Emdogain). A female patient with gingival recession on maxillary central incisors is presented with 4-year follow-up observation. The surgical procedure used in this clinical pilot case study produced a marked reduction in gingival recession that was maintained for 4 years. Initial gingival recession averaged 4.25 mm with a probing depth of 1.25 mm. The 4-year follow-up demonstrated no significant changes in the degree of postoperative results obtained after 1 year. At the 4-year follow-up, a mean of 3.75 mm of root coverage was observed (93.8% root coverage). Probing depth averaged 0.75 mm, indicating a total of 4.25 mm gain of clinical attachment. Within the limits of this case, the results demonstrated the possibility of treating human buccal recessions by means of enamel matrix protein derivative together with the laterally repositioned flap technique, with a predictable reduction in recession and clinical gain in attachment.
Keywords: Female; Humans; Middle Aged; Treatment Outcome; Follow-Up Studies; Surgical Flaps; Pilot Projects; Biocompatible Materials; Gingivoplasty; Dental Enamel Proteins; Gingival Recession